Multi-taxon inventory and landscape characterization in an agrosystem of the Brazilian Midwest targeted for payment for environmental services - Morais, Alessandro R.; Freitas-Oliveira, Roniel; Moreira, Jânio Cordeiro; de Souza, Antonio Olímpio; Bittar, Bruno Barros; de Carvalho, Fábio Martins Vilar; de Oliveira, Gustavo Valtuille; Santos, Lia Raquel Souza; Guimarães, Marco Antônio; Amorim, Nathan Pereira Lima; de Assis, Rhayane Alves [UNESP]; Borges, Rinneu Elias; et al. (FapUNIFESP (SciELO), 2022)
The replacement of natural landscapes by anthropic environments has led to habitat loss and consequently, to the decline and extinction of many species populations. Several strategies, such as the creation of protected areas (PAs) and payment for ecosystem services have been adopted to mitigate the consequences of this biodiversity crisis. In Rio Verde, Goiás, Brazil, a Water Producer Program (WPP) was established, which provides payment for ecosystem services for the maintenance of riparian vegetation in the region of the Ribeirão Abóbora, a river which supplies the city and metropolitan area. In the absence of environmental diagnostic studies in the region, this present study contributes to reducing some knowledge gaps, through the: (i) characterization of the landscape in the WPP area, (ii) characterization of species of fauna (amphibians, birds, fish, and medium and large terrestrial mammals) and woody flora that occur in this area, and (iii) comparison of species diversity (fauna and flora) found in our study area with the diversity observed in the Cerrado protected area network. Our results reveal a low native vegetation cover (~21% of total area), but we recorded 300 total species: 20 species of anuran amphibians, 100 birds, 10 fish, 16 terrestrial mammals (medium and large), and 154 woody plants. Our sample comprises species considered endemic to the Cerrado (e.g., Anuran-Barycholos terntezi and Mammal-Callithrix penicillata), threatened species (e.g., Mammals-Herpailurus yagouaroundi, Myrmecophaga tridactyla and Tapirus terrestris), and exotic invasive species (Mammal-Sus scrofa). The results presented in this study are relevant and may help in the proposal of management actions within the scope of this important program of payment for environmental services.
Inventário multi-táxon e caracterização da paisagem em um agrossistema no Centro-Oeste brasileiro alvo de pagamento por serviços ambientais
Keywords: Anurans; Birds; Exotic invasive species; Fishes; Mammals; Threatened species; Woody plants